Influence of Ambient Temperature on the Intensity of Tread Wear of Large Tires - Yusupov Umidbek Boltayevich; Mukhitdinov Akmal Anvarovich; Tuxtamishov Sobit Sobirovich; Urinbayev Quvondiq Ulug’bek o’g’li (Genius Journals, 2022)
The article presents the results of an experiment conducted on the tires of technological vehicles operated in the Amantai quarry. During the year in a quarry, the dynamics of changes in ambient temperature was studied and its effect on the intensity of tire tread wear was calculated. As a result, on hot days (above 300C), tire operation beyond the capacity of heat dissipation inevitably leads to the formation of internal delaminations, mainly in the shoulder area of the tires.
Keywords: Tire resource; ambient temperature; technological transport